AI Readiness in 21st-Century Islamic Education: Teachers Behavioral Intentions and Perceived Control - Febrianto, Agung; Habibi, Akhmad; Sofyan, Sofyan (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study investigates the determinants of AI adoption among Islamic Religious Education teachers within the 21st-century learning paradigm. Grounded in the TPB, it examines how attitudes, subjective norms, and perceived behavioral control shape teachers’ intentions and actual behaviors regarding AI integration. A quantitative survey was conducted via online questionnaires distributed to 150 islamic religious education teachers in Tanjung Jabung Barat Regency, Jambi. Data were analyzed using SmartPLS 3 for PLS-SEM. Results indicate that perceived behavioral control was the most significant predictor, strongly influencing intention with coefficient = 0.586, p <0.001 and behavior with coefficient = 0.300, p = 0.021. Subjective norms also significantly affected intention with coefficient = 0.278, p = 0.001. Conversely, attitudes had no direct impact on intention (p = 0.681) but significantly predicted behavior with coefficient = 0.432, p <0.001. The model demonstrated strong explanatory power. Accounting for 65.8% of intention variance and 78.9% of behavior variance, affirming TPB’s efficacy in understanding technology adoption among Islamic religious education teachers. These findings underscore the critical role of teachers’ self-efficacy and social influence in AI adoption. Practical interventions, such as hands-on training and fostering supportive environments, are essential for successful integration. Future research could explore mediating variables or qualitative approaches to deepen understanding of barriers and facilitators.